2011
DOI: 10.3832/ifor0566-004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of forest ecosystems to air pollution and climate change: a global assessment on research priorities

Abstract: Climate change and air pollution are two of the anthropogenic stressors that require international collaboration. Influence mechanisms and combating strategies towards them have similarities to some extent. Impacts of air pollution and climate change have long been studied under IUFRO Research Group 7.01 and state of the art findings are presented at biannual meetings. Monitoring, modelling, assessment of multiple stressors, ecophysiology, and nutrient cycles have been thoroughly studied aspects of climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 32 publications
(30 reference statements)
0
41
0
1
Order By: Relevance
“…O 3 has been shown to be harmful to human health, vegetation and certain materials (Bytnerowicz et al, 2007;Serengil et al, 2011). Background concentrations of O 3 in the troposphere have continuously increased since the preindustrial age, although control measures on the emission of its precursors have reduced O 3 peaks (Vingarzan, 2004;Derwent et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…O 3 has been shown to be harmful to human health, vegetation and certain materials (Bytnerowicz et al, 2007;Serengil et al, 2011). Background concentrations of O 3 in the troposphere have continuously increased since the preindustrial age, although control measures on the emission of its precursors have reduced O 3 peaks (Vingarzan, 2004;Derwent et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric ozone (O 3 ) is recognized as a significant phytotoxic air pollutant and greenhouse gas (Bytnerowicz et al, 2007;Serengil et al, 2011). Ozone concentrations have been increasing in the northern hemisphere since the pre-industrial age (Akimoto, 2003;Vingarzan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A critical analysis of the meta-database made it possible to identify current knowledge gaps and showed that: in many regions ground-level ozone is under-investigated, although it is one of the pollutants of greatest concern to forests (Serengil et al, 2011); in addition to CO 2 , long-term flux measurements of other greenhouse gases (GHGs) should be carried out; there is still a need of improving links between monitoring of atmospheric changes and impacts on forests because these two fundamental activities are typically carried out separately in independent ERNs; and research-oriented manipulative experiments in the forests are missing (Danielewska et al, 2013a). The meta-database described above was created on the basis of major research and monitoring networks in Europe, but it cannot replace existing databases; it merely improves access to and coordination between the different datasets.…”
Section: Main Achievements On Availability and Evaluation Of Monitorimentioning
confidence: 99%